Pengembangan Model Pembelajaran Matematika Berbasis Masalah Kontekstual untuk Meningkatkan Kemampuan Berpikir Kritis Siswa pada Materi Sistem Persamaan Linear Dua Variabel - Rangu, Martinus Darto; Astawa, I Wayan Puja; Putu Suharta, I Gusti (Literasi: Jurnal Pendidikan Guru Indonesia, 2025)
This research aims to develop a valid, practical and effective contextual problem-based mathematics learning model to improve students' critical thinking skills. This type of research is a research on the development of a plomp which consists of three stages, namely preliminary research, prototyping stage and assessment stage. The research was conducted at Widya Sakti Junior High School in Denpasar. The data of this study was obtained through observation, interviews, questionnaires, and critical thinking ability tests, The results of this study show that: 1). The developed learning model has met the valid criteria with an average score of 10.32. based on expert assessment 2). The level of practicality of the learning model of the teacher response questionnaire with an average score of 46.25% with practical criteria and the average student response questionnaire score of 6.0%, with practical criteria and field trials of teacher response questionnaires with an average score of 50.25 with very practical criteria and student response questionnaires with an average score of 8.33% with very practical criteria, 3). The level of effectiveness of students' critical thinking skills from the results of the pre-test score is an average score of 50.20% with the effective criteria, and the results of the post-test score is an average score of 82.50% with very effective criteria, Based on these findings, it can be concluded that the development of a mathematics learning model based on contextual problems has met the valid, practical and effective criteria to be able to improve students' critical thinking skills